1970
DOI: 10.1039/c29700000054
|View full text |Cite
|
Sign up to set email alerts
|

2,2′-Bipyridyl and o-phenanthroline carbonyl complexes of rhodium

Abstract: Two new carbonyl complexes of rhodium, [Rh(CO) , bipy]ClO, and [Rh(CO) ,o-phen]ClO, have been prepared. EARLIER attempts to prepare 2,2 '-bipyridyl and o-phenanthroline carbonyl complexes of rhodium have yielded only the binuclear complex [Rh(CO) ,Cl],(bipy). Though the formation of some mononuclear complexes was also suspected such complexes were not actually iso1ated.l Two new carbonyl complexes of rhodium, [Rh(CO), bipyl-ClO, (I) and [Rh(CO),o-phenIC10, (11), have now been Compound8 [Rh(CO), bipylCl0,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Cations of the Type RhL4+ and RhL6+.-The dimer quartet; m, multiplet; b, broad. 6 Resonance pattern as shown in Figure 1; J is the separation of outer peaks. 6 Ill-defined peak.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cations of the Type RhL4+ and RhL6+.-The dimer quartet; m, multiplet; b, broad. 6 Resonance pattern as shown in Figure 1; J is the separation of outer peaks. 6 Ill-defined peak.…”
Section: Resultsmentioning
confidence: 99%
“…6 Resonance pattern as shown in Figure 1; J is the separation of outer peaks. 6 Ill-defined peak. rapidly dissolves in this solvent in the presence of a sixto eightfold excess of the ligands L = P^-f-CaH^a, In contrast to those discussed above, the reactions of [C8Hi2RhCl]2 with a sixto eightfold excess of the tertiary phosphite ligands L = P(OR)3 (R = CH3, C2H6, LC4H9, and m-C4H9) and P(OCH2)3CCH3 in methanol at room temperature followed by the addition of sodium tetraphenylboron yielded the five-coordinate rhodium(I) derivatives [RhL5]B(C6HE)4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 As is well known, p-aminophenol (4-AP) is an important intermediate and a main ingredient in the synthesis of various analgesic and antipyretic drugs. 6 Its synthesis usually involves the reduction of 4-NP in the presence of sodium borohydride (NaBH 4 ) with the assistance of diverse catalysts. [7][8][9] And this process is generally performed in aqueous solution under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In Reddy' work, gold nanoparticles were used for the catalytic reduction of 4-NP, which took 23 min. 6 Tang et al synthesized a novel catalyst Sb 2 Se 3 /TNAs, but the conversion rate of 4-NP was just 93.5%, taking 80 min. 6 Qiu et al reported that magnetic chitosan/Fe 3 O 4 composites transformed 4-NP to 4-AP completely within 1.5 h. 10 Liu studied the catalytic activity of Au/PAN nanofibrous membranes for the reduction of 4-NP, the whole process lasting about 3.5 h. 11 Clearly, these catalysts take a relatively long time and their catalytic effects are poor.…”
Section: Introductionmentioning
confidence: 99%